ISLAMIC EDUCATION VALUE IN THE PROCESS OF MANEJEK HUMA (MEMBANGUN RUMAH) FOR DAYAK KAHAYAN / NGAJU (BIAJU) AT BAHAUR HULU VILLAGE - Heni Rianti; Syaipullah Syaipullah; Muslimah Muslimah; Hamdanah Hamdanah (Journal of Contemporary Islamic Education, 2021)
The aim of this research was to know how the process Manejek Huma in the Dayak culture of kahayan / ngaju (biaju) in Bahaur Hulu Village and to analyze the values of Islamic education in the process of Manejek Huma in Dayak Kahayan / ngaju (biaju) Tribe at Bahaur Hulu Village. This research used an ethnographic approach. In collecting data the researchers used observation, interview and documentation. The result show that the Islamic education value in the process of mockinghuma the Dayak Kahayan / Ngaju was reading basmallah, praying, reading the Qur'an praying and giving thanks to Allah, always giving respect to the Prophet Muhammad SAW. The indigenous culture and customs and traditions of this tribe have absorbed a lot from the culture and customs of the Banjar Malay tribe. Keyword : Islamic Educaion ValueIslamic Educaion Value; Manajek Huma; Dayak Kahayan/Ngaju (Biaju)